Transvaginal evisceration of the small bowel a rare and potentially lethal event, a case report. (May 2021) - Negrete, Jose R.; Molina, Gabriel A.; Sanchez, Andrea C.; Caiza, Edwin; Acosta, Cesar; Alvear, Maria de Lourdes; Gonzalez, Hernán; Zavalza, Juan F.
Abstract: Introduction and Importance: Evisceration of the small bowel through the vagina is an extremely rare condition and a life-threatening surgical emergency. Complications associated with this condition include bowel ischemia, abdominal sepsis, and deep vein thrombosis. Therefore, prompt surgical consultation and treatment are crucial as delay in treatment can lead to a grim outcome. Case presentation: We report the case of a 50-year-old female obese patient with a past medical history of uterine surgery. During a cough episode, she experienced sudden transvaginal evisceration that required emergent surgery. Thankfully she fully recovered and is doing well. Discussion and conclusions: Transvaginal evisceration is a life-threatening and extremely rare pathology; it requires urgent diagnosis and surgical intervention since bowel viability can be compromised. During these rare events, interdisciplinary surgical cooperation is vital to obtain the best possible outcome for patients. Highlights: Transvaginal evisceration is a life-threatening and extremely rare pathology. Prompt surgical consultation is crucial as delay in treatment can lead to sever complications. Complications associated with this condition include bowel ischemia, abdominal sepsis, and deep vein thrombosis.